Optimization of the thickness of a conducting polymer, polyaniline, deposited on the surface of poly(vinyl chloride) membranes: a new way to improve their potentiometric response - Shishkanova, T V; Matejka, P; Král, V; Sedenková, I; Trchová, M; Stejskal, J (Analytica chimica acta, 2008)
Repeated depositions of polyaniline (PANI) have been used to control the thickness of the polymeric film deposited on poly(vinyl chloride) (PVC) membrane surface. The oxidation of aniline was carried out in a dispersion mode, i.e. in the presence of poly(N-vinylpyrrolidone) (PVP). Two kinds of PVC were used for this purpose: a non-plasticized PVC for the study of PANI deposition and PVC, plasticized with nitrophenyl octyl ether (NPOE), as a prototype of a liquid membrane electrode. The results of UV-visible and FTIR spectroscopies and electron microscopy showed that (1) the film thickness increased by about equal increments of approximately 40 nm after each polymerization, and (2) the interface with PVC was constituted by PANI film and adhering PANI-PVP colloidal particles. The various thicknesses of the deposited PANI films affected the potentiometric response of the NPOE/PVC membrane with and without an anion-exchanger. The potentiometric anionic response was observed with a minimal thickness of PANI film on the blank NPOE/PVC membrane. Sensitivity of the PANI film to pH occurred only with a blank NPOE/PVC membrane coated with a thick polymeric film, while it was strongly suppressed by the presence of a lipophilic anion-exchanger, tridodecylmethylammonium chloride (TDDMACl), in the membrane, regardless of the thickness of the polymer film. The thickness of the PANI film did not affect the anionic selectivity pattern of TDDMACl-based membranes to any great extent, but its presence improved and stabilized their potentiometric characteristics (sensitivity, linear-response range).